Technology of building adaptive graphical web interfaces for data editing (ADVANCED TECHNOLOGIES AND COMPUTER SCIENCE, 2021)
The article discusses the technology of creating and modifying data in a heterogeneous information system using adaptive graphical web interfaces. The purpose of the work is to create a set of technical developments and techniques that implement a systematic and integrated approach to the construction of adaptive user interfaces. The research method is based on a systematic analysis of modern technologies for creating adaptive graphical interfaces, developing their own technology and testing it experimentally. A server-side Web application has been developed that provides on-screen forms for creating and editing XML documents in accordance with the selected XSD schema. On-screen forms are generated on the server side and are provided to the user as HTML pages. The field of application of the above-mentioned technology is the integration of the created adaptive graphical web interface in a distributed information system in order to increase the efficiency of user access to heterogeneous information and the ability to manipulate it.